Current Treatments and Innovations in Diabetic Retinopathy and Diabetic Macular Edema - Jesus H. Gonzalez-Cortes; Victor A. Martinez-Pacheco; Jesus E. Gonzalez-Cantu; Alper Bilgic; Francesc March de Ribot; Aditya Sudhalkar; Jesus Mohamed-Hamsho; Laurent Kodjikian; Thibaud Mathis (MDPI AG, 2022)
Diabetic retinopathy (DR) is one of the leading causes of blindness worldwide. Multiple treatment options have been used over time to attempt to modify the natural progression of the disease in both proliferative diabetic retinopathy (PDR) and diabetic macular edema (DME). These two retinal complications are the result of microvascular occlusions and vascular hyperpermeability and are considered one of the leading causes of irreversible blindness in patients of working age. It is now well demonstrated that PDR and DME are associated with increased levels of inflammatory and pro-angiogenic factors in the ocular compartment. To date, laser photocoagulation, vascular endothelial growth factor (VEGF) inhibitors, and corticosteroids have demonstrated efficacy in their treatment in large randomized controlled trials and in real-life observational studies. This manuscript aims to provide a comprehensive review of current treatments, including the main drugs used in diabetic pathologic manifestations, as well as new therapeutic alternatives, such as extended-release intraocular devices.